Excretory/secretory-products of Echinococcus multilocularis larvae induce apoptosis and tolerogenic properties in dendritic cells in vitro. - Justin Komguep Nono; Katrien Pletinckx; Manfred B Lutz; Klaus Brehm (PLoS Neglected Tropical Diseases)
Background Alveolar echinococcosis, caused by Echinococcus multilocularis larvae, is a chronic disease associated with considerable modulation of the host immune response. Dendritic cells (DC) are key effectors in shaping the immune response and among the first cells encountered by the parasite during an infection. Although it is assumed that E.multilocularis, by excretory/secretory (E/S)-products, specifically affects DC to deviate immune responses, little information is available on the molecular nature of respective E/S-products and their mode of action. Methodology/principal findings We established cultivation systems for exposing DC to live material from early (oncosphere), chronic (metacestode) and late (protoscolex) infectious stages. When co-incubated with Echinococcus primary cells, representing the invading oncosphere, or metacestode vesicles, a significant proportion of DC underwent apoptosis and the surviving DC failed to mature. In contrast, DC exposed to protoscoleces upregulated maturation markers and did not undergo apoptosis. After pre-incubation with primary cells and metacestode vesicles, DC showed a strongly impaired ability to be activated by the TLR ligand LPS, which was not observed in DC pre-treated with protoscolex E/S-products. While none of the larvae induced the secretion of pro-inflammatory IL-12p70, the production of immunosuppressive IL-10 was elevated in response to primary cell E/S-products. Finally, upon incubation with DC and naïve T-cells, E/S-products from metacestode vesicles led to a significant expansion of Foxp3+ T cells in vitro. Conclusions This is the first report on the induction of apoptosis in DC by cestode E/S-products. Our data indicate that the early infective stage of E. multilocularis is a strong inducer of tolerance in DC, which is most probably important for generating an immunosuppressive environment at an infection phase in which the parasite is highly vulnerable to host attacks. The induction of CD4+CD25+Foxp3+ T cells through metacestode E/S-products suggests that these cells fulfill an important role for parasite persistence during chronic echinococcosis.